Trilhas digitais usos das redes sociais online: por onde navegam as mulheres ricas, na casa dos trinta anos, moradoras de São Paulo? - Semino, Natalia (2017)
This qualitative research, of participant observation, seeks to understand through the use of Anthropology the unfolding of the subjectivity of rich women of the age of thirty to forty, who are users of online social networks and live in São Paulo. The research observed the use of online social networks and the unfolding of usage in daily life. Participants were identified using a snowball methodology, which resulted in the interview of nine women. Interviews took place over two to three meetings; two individual meetings and one in-group. During the first meeting a semi-structured interview technique was used. In the second meeting I requested a graphic production explaining the uses of online social networks, which made possible for a more focused conversation. The third meeting used a focus group technique and intended to broaden the understanding of the participants. The interviews were transcribed and the Content Analysis was used as data collection methodology. The results led us to understand that the use of online social networks on the one hand negatively impacts the subjectivity of women, because through the content consumed they absorb and structure patriarchal references, oppressive creativity as to the social roles played, (re) stigmatizing as beautiful, maternal, hard worked, happy and wives. On the other hand, recreational uses break with the ruthless lists of tasks that need to be performed, because despite the financial contribution, these women are charged for playing the roles previously mentioned, and surfing online social networks is an action that breaks this flow and contributes to greater gender equity. This would certainly be more functional if it were not for the kind of content that further strengthens the stigmas in the way they understand each other in the world